Multidimensional assessment of sustainability and competitiveness in the ceramic tile and natural stone industries: a cross-country comparative study - Reza Yarahmadi; Ali Asghar Asadi (Scientific Reports)
Abstract Natural stone and ceramic tile industries are two of the leading competitors in the global building materials sector. This study employs a multidimensional and integrative framework to conduct a comprehensive comparative analysis of these strategic industries across seven selected countries. The assessment simultaneously examines their economic, environmental, organizational, and industrial performance. To achieve this, the study integrates classical decision-making tools, namely Life Cycle Costing (LCC), SWOT analysis, and Porter’s Five Forces, with modern machine learning techniques, including Principal Component Analysis (PCA), K-Means clustering, and SHAP. Five key indicators, production cost, energy consumption, CO₂ emission intensity, water usage, and non-recyclable waste generation, were sourced from authoritative international datasets, normalized, and comparatively analyzed. PCA results revealed that the first principal component reflects economic-energy intensity, while the second captures environmental burden. K-Means clustering classified countries into three structural categories: sustainable industrial economies, semi-sustainable states, and high-risk developing economies. SHAP analysis, applied to a multivariate regression model, identified CO₂ emissions as the most influential factor driving structural pressure, highlighting its significance in climate-focused policymaking. The LCC results further demonstrated that although natural stone entails higher initial installation costs, it proves more cost-effective over the long term compared to ceramic tile. From an organizational standpoint, findings show that in advanced economies, the ceramic tile sector benefits from skilled labor, high levels of technological integration, and institutional maturity. In contrast, the natural stone industry, particularly in developing nations, faces challenges such as low-skilled workforces, regulatory complexity, and cultural resistance to innovation.